Neoadjuvant trastuzumab, pertuzumab, and chemotherapy versus trastuzumab emtansine plus pertuzumab in patients with HER2-positive breast cancer (KRISTINE): a randomised, open-label, multicentre, phase 3 trial. Issue 1 (January 2018) - Hurvitz, Sara A; Martin, Miguel; Symmans, W Fraser; Jung, Kyung Hae; Huang, Chiun-Sheng; Thompson, Alastair M; Harbeck, Nadia; Valero, Vicente; Stroyakovskiy, Daniil; Wildiers, Hans; Campone, Mario; Boileau, Jean-François; et al.
Summary: Background: HER2-targeted treatments have improved outcomes in patients with HER2-positive breast cancer in the neoadjuvant, adjuvant, and metastatic settings; however, some patients remain at risk of relapse or death for many years after treatment of early-stage disease. Therefore, new strategies are needed. We did a phase 3 trial to assess a neoadjuvant regimen for HER2-positive breast cancer that replaces traditional systemic chemotherapy with targeted treatment. Methods: We did a randomised, open-label phase 3 KRISTINE trial in 68 Translational Research In Oncology centres (hospitals and specialty cancer centres in Asia, Europe, USA, and Canada). Eligible participants were aged 18 years or older with centrally confirmed HER2-positive stage II–III operable breast cancer (>2 cm tumour size), an Eastern Cooperative Oncology Group performance status of 0–1, and a baseline left ventricular ejection fraction of at least 55% (by echocardiogram or multiple-gated acquisition scan). We randomly assigned participants (1:1) to receive either trastuzumab emtansine plus pertuzumab or docetaxel, carboplatin, and trastuzumab plus pertuzumab. We did the randomisation via an interactive response system under a permuted block randomisation scheme (block size of four), stratified by hormone receptor status, stage at diagnosis, and geographical location. Patients received six cycles (every 3 weeks) of neoadjuvant trastuzumab emtansine plus pertuzumab (trastuzumab emtansine 3·6 mg/kg; pertuzumab 840 mg loading dose, 420 mg maintenance doses) or docetaxel, carboplatin, and trastuzumab plus pertuzumab (docetaxel 75 mg/m 2 ; carboplatin area under the concentration–time curve 6 mg/mL × min; trastuzumab 8 mg/kg loading dose, 6 mg/kg maintenance doses) plus pertuzumab [same dosing as in the other group]). All treatments were administered intravenously. The primary objective was to compare the number of patients who achieved a pathological complete response (ypT0/is, ypN0), between groups in the intention-to-treat population (two-sided assessment), based on local evaluation of tumour samples taken at breast cancer surgery done between 14 days and 6 weeks after completion of neoadjuvant therapy. Safety was analysed in patients who received at least one dose of study medication. This trial is registered with ClinicalTrials.gov, number NCT02131064, and follow-up of the adjuvant phase is ongoing. Findings: Between June 25, 2014, and June 15, 2015, we randomly assigned 444 patients to neoadjuvant treatment with trastuzumab emtansine plus pertuzumab (n=223) or docetaxel, carboplatin, and trastuzumab plus pertuzumab (n=221). A pathological complete response was achieved by 99 (44·4%) of 223 patients in the trastuzumab emtansine plus pertuzumab group and 123 (55·7%) of 221 patients in the docetaxel, carboplatin, and trastuzumab plus pertuzumab group (absolute difference −11·3 percentage points, 95% CI −20·5 to −2·0; p=0·016). During neoadjuvant treatment, compared with patients receiving docetaxel, carboplatin, and trastuzumab plus pertuzumab, fewer patients receiving trastuzumab emtansine plus pertuzumab had a grade 3–4 adverse event (29 [13%] of 223 vs 141 [64%] of 219) or a serious adverse event (11 [5%] of 223 vs 63 [29%] of 219). The most common grade 3–4 adverse events in the trastuzumab emtansine plus pertuzumab group were decreased platelet count (three [1%] of 223 patients vs 11 [5%] of 219 with docetaxel, carboplatin, and trastuzumab plus pertuzumab), fatigue (three [1%] vs seven [3%]), alanine aminotransferase increase (three [1%] vs four [2%]), and hypokalaemia (three [1%] vs five [2%]). The most common grade 3–4 adverse events in the docetaxel, carboplatin, and trastuzumab plus pertuzumab group were neutropenia (55 [25%] of 219 vs one [<1%] of 223 with trastuzumab emtansine plus pertuzumab), diarrhoea (33 [15%] vs 2 [<1%]), and febrile neutropenia (33 [15%] vs 0). No deaths were reported during neoadjuvant treatment. Interpretation: Traditional neoadjuvant systemic chemotherapy plus dual HER2-targeted blockade (docetaxel, carboplatin, and trastuzumab plus pertuzumab) resulted in significantly more patients achieving a pathological complete response than HER2-targeted chemotherapy plus HER2-targeted blockade (trastuzumab emtansine plus pertuzumab); however, numerically more grade 3–4 and serious adverse events occurred in the chemotherapy plus trastuzumab and pertuzumab group. Further efforts to improve the efficacy of chemotherapy without imparting more toxicity are warranted. Funding: F Hoffmann-La Roche and Genentech.